Bedtime Stories: Audiobooks, Podcasts, and Reading as Listening (and Sleeping) - Dittrich, Josh (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2023)
This essay approaches sleep podcasts as bedtime stories, exploring the contradictory phenomenology of reading and listening while falling asleep. The first part categorizes audiobook and podcast listening as aural reading through an expanded definition of aurality and a logic of mediated self-control. The essay then proposes a concept of so(m)niferous reading to describe the paradoxical audio-textual inattentiveness that mediates the experience of going to sleep in a typical sleep podcast like Drew Ackerman’s Sleep With Me (2013). Finally, the essay contextualizes the so(m)niferous reading of audiobooks/podcasts in the discourse of children’s bedtime stories, raising critical questions about the subjectivity and agency of so(m)mniferous readers in the contemporary sleepscape.